PERAHU LANCANG KUNING KEARIFAN LOKAL MASYARAKAT MELAYU BINTAN KEPULAUAN RIAU - Samin, Rumzi; Khodijah, Khodijah (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2018)
The Lancang Kuning boat research that is oriented to Identification, documentation, Inventory, data and local wisdom and the use of technology that has local nuances on a provincial scale that is more maritime oriented. Therefore this research is in line with the RIP Lancang Kuning local wisdom of the Malay people of Bintan Riau Islands